(untitled) (Research, Society and Development, 2022)
The biofloc system (biofloc technology - BFT) has high efficiency in the production of aquatic organisms and with low polluting potential. Its principle is the heterotrophic bacteria growth, obtained by maintaining the carbon: nitrogen (C: N) ratio in the medium, which will transform undesirable componentes, such as ammonia and nitrite, into less toxic compounds and with some protein value. This system consists of maintaining the carbon: nitrogen ratio (C: N). The main constitution of bioflocs are microalgae, feces, exoskeletons, feed and dead animal remains, bacteria, rotifers, protozoa, other invertebrates, in complex interaction in the water column. This work aimed to evaluate the variation of water quality, the zooplanktonic biomass present in the BFT formed with three carbon: nitrogen ratios, as well as to verify diferences in maturation time among C: N ratios. The bioflocs were formed using refined sugar as a carbon source, three treatments were tested with different carbon: nitrogen ratios, 10: 1, 15: 1 and 20: 1. Ammonia, nitrite, nitrate, orthophosphate, alkalinity, temperature, dissolved oxygen and pH were measured at intervals of 3 to 4 days. The physical and chemical parameters of the water showed no significant differences between treatments, with the exception of orthophosphate, which showed a difference in treatment 20: 1. The maturation of the 20: 1 treatment occurred only 3 days after the maturation of the 10: 1 and 15: 1 treatment and the zooplanktonic density did not differ among treatments. It is recommended to use the 10: 1 carbon: nitrogen ratio, since there will be an economy in the amount of carbon offered to the medium and, consequently, a lower production cost.